1989
DOI: 10.1099/00222615-30-1-23
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antibodies to common antigens of pathogenic and commensal Neisseria species

Abstract: Summary. Sera from 29 children and six adults were used to investigate the nature of antigenic cross-reactivity between Neisseria polysaccharea, N . lactamica and N . meningitidis B, 15P1.16 by immunoblotting. Major common antigens of 68-70 Kda, 60-65 Kda and 15-20 Kda were detected. Antibody directed against them uniformly decreased after absorption of the sera with the three different Neisseria species. Antigens of 55 Kda and 35 Kda specific to N . meningitidis, and one of 43 Kda specific to N . lactamica, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Further, the mechanisms for the induction of immunity to meningococcal disease by N. lactamica carriage have not been established. It has been documented that antibodies that are cross-reactive against meningococci are present in infants after carriage of N. lactamica (6,21,22), and it has been suggested that bacterial interference is a protective factor, with the more predominant N. lactamica inhibiting colonization by N. meningitidis (21). If this is correct, then the widespread intentional colonization by N. lactamica strains could enhance natural protection (23) and inhibit colonization by N. meningitidis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the mechanisms for the induction of immunity to meningococcal disease by N. lactamica carriage have not been established. It has been documented that antibodies that are cross-reactive against meningococci are present in infants after carriage of N. lactamica (6,21,22), and it has been suggested that bacterial interference is a protective factor, with the more predominant N. lactamica inhibiting colonization by N. meningitidis (21). If this is correct, then the widespread intentional colonization by N. lactamica strains could enhance natural protection (23) and inhibit colonization by N. meningitidis.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of carriage and population diversity of N. lactamica will influence any immunity to meningococcal disease that is generated by the asymptomatic carriage of this commensal during infancy (6,21,22). As N. lactamica is acapsulate (22), this immunity would have to be active against subcapsular components of the meningococcus, and given the antigenic and genetic diversity of the meningococcal populations (10), any active protection induced by N. lactamica would also have to be cross-protective against many meningococcal strains.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that acquisition of natural immunity in young children may follow colonization by nonpathogenic species of Neisseria and some other bacteria expressing immunologically cross-reactive surface antigens shared with meningococci (13). Epidemiological evidence suggests that N. lactamica, a commensal species that does not possess a polysaccharide capsule and has common antigens with N. meningitidis (4,17), may be the most important of these.…”
mentioning
confidence: 99%
“…More The two species N. lactamica and N. meningitidis share numerthan 99% of 250 meningococcal strains reacted with a mouse ous membrane proteins with cross-reactive antigenicity. [176][177][178][179][180] monoclonal antibody directed at NspA, and passive and active Recently, the injection of killed whole cells of N. lactamica or its protection was demonstrated in mice against experimental infecOMPs has been shown to protect mice against a lethal challenge tion with meningococci of serogroups A, B, and C. [196] Focusing with N. meningitidis of various strains. [181] Interestingly, this ocon serogroup B meningococcal strains, other researchers could not curred despite the absence of serum bactericidal activity, which fully replicate these findings: [197] 35% of strains did not react with suggests that other mechanisms (such as opsonophagocytosis) polyclonal anti-NspA antibodies despite the expression of NspA may be the predominant protective mechanism in this model.…”
Section: Group B Polysaccharide Vaccinesmentioning
confidence: 99%